Antiviral activity of Thiosemicarbazones derived from α‐amino acids against Dengue virus. Issue 3 (9th August 2016) - Padmanabhan, Padmapriya; Khaleefathullah, Sheriff; Kaveri, Krishansamy; Palani, Gunasekaran; Ramanathan, Giriprasath; Thennarasu, Sathiah; Tirichurapalli Sivagnanam, Uma
Abstract : The endemicity and seasonal outbreaks of Dengue disease in most tropical and subtropical countries underscores an urgent need to develop effective prevention and control measures. Development of a Dengue vaccine, which is complicated by the Antibody Dependent Enhancement effect (ADE), a viral inhibitor, seems prudent as it would inhibit the spread of the virus. In vitro methods such as MTT assay and plaque formation unit reduction assays were employed for screening the viral inhibitory property of α‐amino acid based Thiosemicarbazides. The results elicits that at concentrations not exceeding the maximum non cytotoxic concentration (MNCC), these compounds completely prevented Dengue virus infection in vero cells as indicated by the absence of cytopathic effects in a dose‐dependent manner. The high potency of Bz‐Trp‐TSC against all four types of Dengue virus infection elevates Thiosemicarbazide as a lead antiviral agent for Dengue disease. Screening small molecules for antiviral activity against the most rapidly spreading mosquito‐borne viral disease is being explored by several research groups. Our findings would help to augment the efforts to identify the lead compounds for antiviral therapy to combat the Dengue disease. J. Med. Virol. 89:546–552, 2017 . © 2016 Wiley Periodicals, Inc.